PENGARUH PSIKOSOSIAL TERHADAP RISIKO MENGEMUDI YANG DIMEDIASI OLEH KELELAHAN PADA SUPIR MINI BUS DI BANDA ACEH – LANGSA - Muhammad Rizky Maulana; Nurdasila Nurdasila (Departemen Manajemen, 2019)
This study aims to measure the Psychosocial Effects of Driving risks mediated by fatigue of mini bus drivers in Banda Aceh - Langsa. The sample used in this study was a mini bus driver in Banda Aceh - Langsa numbered 110 respondents. Data collection equipment used in this study was a questionnaire. Sampling technique used in this research is convenience sampling. Regression method hierarchical linear models (HLM) are used as an analysis method for know the effect of all the variables involved. Based on analysis results, indicate that psychosocial influence on risk Driving, Psychological influence on Fatigue, Risk of Driving effect on Fatigue, Psychosocial influence on Risk Driving mediated by fatigue.